Analisis Wacana Kritis Puisi “Munajat 212” Karya Neno Warisman Analisis Model Teun A. Van Dijk - Astri Wijayanti; Bambang Djunaidi; Suryadi Suryadi (LP4MK STKIP PGRI Lubuklinggau, 2020)
This research was aimed to describe the text structure, social cognition and social context in the poem “Munajat 212” by Neno Warisman. The theory used is Critical Discourse Analysis by Teun A. Van Dijk's model which has three dimensions. Analysis of text structure, social cognition, and social context. The method used is descriptive method. The research data were obtained through internet searches related to manuscripts and video documentation of the reading of the poem